Towards the identification of the scale insects (Hemiptera: Coccomorpha) of continental Africa: 1. Identification of the families - Watson, Gillian W.; Ouvrard, David (Zootaxa, 2021)
Scale insects (Hemiptera: Sternorrhyncha: Coccomorpha) are obligate plant parasites feeding on plant sap; some are damaging pests in agriculture, horticulture and forestry. Despite their economic importance, the scale insects found in continental Africa have not been extensively studied and the keys for identifying them are incomplete and scattered through the literature in several languages. The aim of this study is to improve our understanding of the African scale insect fauna. As a first step towards their identification, we provide a key to the 23 families currently known from continental Africa, based on slide-mounted adult females, covering Aclerdidae, Asterolecaniidae, Cerococcidae, Coccidae, Conchaspididae, Dactylopiidae, Diaspididae, Eriococcidae, Halimococcidae, Kermesidae, Kerriidae, Kuwaniidae, Lecanodiaspididae, Margarodidae, Matsucoccidae, Micrococcidae, Monophlebidae, Ortheziidae, Phoenicococcidae, Pseudococcidae, Putoidae, Rhizoecidae and Stictococcidae.